Efficacy and Safety of Intra-articular Injections of Hyaluronic Acid Combined With Polydeoxyribonucleotide in the Treatment of Knee Osteoarthritis - Yoon, Seihee (Ann Rehabil Med, 2019)
OBJECTIVE: To assess the clinical efficacy and safety of intra-articular injection of hyaluronic acid (HA) combined with polydeoxyribonucleotide (PDRN) in patients with knee osteoarthritis in comparison with that of HA alone. METHODS: The current single-center, prospective, randomized, double-blind, controlled study was conducted in 36 patients with knee osteoarthritis at our medical institution. All the eligible patients (n=30) were equally assigned to two treatment arms (trial group ‘HA+PDRN’ and control group ‘HA’). For efficacy assessment, the patients were evaluated for the visual analogue scale (VAS) scores, the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) and the Knee Society Scores (KSS), all of which served as efficacy outcome measures. We monitored time-dependent changes in efficacy outcome measures at baseline and 1, 3 and 6 months. Subsequently, we compared differences in changes in efficacy outcome measures at 6 months from baseline between the two groups. Moreover, we assessed the safety based on the treatment-emergent adverse events (TEAEs), adverse drug reactions (ADRs) and any other complications serving as safety outcome measures. RESULTS: There were significant differences in changes in the VAS scores, the WOMAC scores in all domains, except ‘Stiffness’, the total WOMAC scores, and the KSS scores in all the domains at 6 months from baseline between the two groups (p<0.05). In our series, there were no TEAEs, ADRs, and any other complications. CONCLUSION: Intra-articular injections of HA combined with PDRN can also be considered in the treatment of knee osteoarthritis. However, further large-scale and multi-center studies are required to demonstrate the potential of the proposed combination.